Pengaruh Labelisasi Halal dan Brand Image Terhadap Minat Beli Produk Wardah Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Makassar - Amaliyah Kamaruddin; Aulia Aulia; Sherry Adelia Natsir Kalla (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This Study is a quantitative research. This study aims to determine the effect of Halal Labeling and Brand Image on the Purchase Intention of Wardah cosmetic products in Student of the Faculty of Economic and Business, Muhammadiyah University of Makassar. The population in this study were students who had used Wardah cosmetic products. The sample used in this study was 100 respondents. The sampling technique using Purpsive Sampling. The instrument used in this study was a questionnaire. The data analysis technique used in this research include validity tests, reliability tests, classic assumption tests, multiple linear regression analysis, t-test, and coefficient of determination (R2). The results of this study indicate that the Halal Labeling variable (X1) has a significant effect on Purchase Intention with a significance value of 0.000 < 0.05. Meanwhile, the Brand Image variable (X2) has a positive and significant effect on Purchase Intention (Y) with a significance value of 0,000 < 0.05. Keywords : Halal Labeling, Brand Image, Purchase Intention